2017
DOI: 10.3389/fpls.2017.02131
|View full text |Cite
|
Sign up to set email alerts
|

Possible Interactions between the Biosynthetic Pathways of Indole Glucosinolate and Auxin

Abstract: Glucosinolates (GLS) are a group of plant secondary metabolites mainly found in Cruciferous plants, share a core structure consisting of a β-thioglucose moiety and a sulfonated oxime, but differ by a variable side chain derived from one of the several amino acids. These compounds are hydrolyzed upon cell damage by thioglucosidase (myrosinase), and the resulting degradation products are toxic to many pathogens and herbivores. Human beings use these compounds as flavor compounds, anti-carcinogens, and bio-pestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 190 publications
(306 reference statements)
2
57
0
Order By: Relevance
“…, and TRYPTOPHAN SYNTHASE α1 were chosen that are involved in tryptophan synthesis, an IAA precursor, and CYP79B2, CYP79B3, NITRILASE1 (NIT1), and NIT2 implicated in the indole-3-acetaldoxime pathway (Malka and Cheng 2017). The expression of all seven selected genes was repressed in the shoot upon ANE treatments.…”
Section: Molecular Analysis Of Ane-induced Plant Growth Promotion In mentioning
confidence: 99%
“…, and TRYPTOPHAN SYNTHASE α1 were chosen that are involved in tryptophan synthesis, an IAA precursor, and CYP79B2, CYP79B3, NITRILASE1 (NIT1), and NIT2 implicated in the indole-3-acetaldoxime pathway (Malka and Cheng 2017). The expression of all seven selected genes was repressed in the shoot upon ANE treatments.…”
Section: Molecular Analysis Of Ane-induced Plant Growth Promotion In mentioning
confidence: 99%
“…Our quantification analysis demonstrated that the contents of IAA and IAA‐Glc, IAA‐Asp, I3C, oxIAA, and IAN significantly increased in yucca‐d (Figure ). This observation provided insight into the regulation of the biosynthetic pathway of IAAs caused by their over‐accumulation. In contrast, IAA‐Ala and Trp were similarly accumulated in the WT and yucca‐d plants, whereas GBR, a metabolite derived from tryptophan, decreased in yucca‐d (Figure ).…”
Section: Resultsmentioning
confidence: 89%
“…These TFs function in regulation of GLS biosynthesis while MYB 51 involved in indole GLS biosynthesis and MYB76 involved in aliphatic GLS biosynthesis. They increase insect resistance in crops (Malka and Cheng 2017) and can be considered as two key regulatory TFs in resistance to insect attacks (Gigolashvili et al 2009) in cotton, as G. hirsutum and G. raimondii show more resistance to such stress. However, further expression analysis to disclose their function in response to insect attack in cotton species is necessary.…”
Section: Insect Related Transcription Factors Are Common Between the mentioning
confidence: 99%